Common sense and sensory perception in avicenna's psycholinguistics: a comparative study of Western and Muslim scholars - Ali, Asem Shehadeh Saleh; Ibnian, Mohamed Ali Musa (Asian Journal of Education, Humanities and Social Science, 2025)
The world has witnessed significant scientific advancements from ancient times to the present. While many attribute these advancements to Western scientists, much of this knowledge was developed by Muslim scholars. Among these contributions is the field of psycholinguistics, in the concepts of common sense and sensory perception. This study aims to identify Avicenna's concepts of common sense and sensory perception and to highlight the differences between his views and those of the Western scholar Aristotle. Using a descriptive-comparative approach, the study involved reviewing articles, previous research. The study concludes with several key findings: Avicenna developed a comprehensive theory of common sense, viewing it as a force operating in the brain's frontal region that receives sensory images and transmits them to the imagination. He asserts that common sense responds to but does not retain these images. The distinction between Avicenna and Aristotle lies in their understanding of common sense: Avicenna posits an inner sense that integrates external senses, while Aristotle sees it as a unification of the external senses. Additionally, the study identifies four main elements of sensory perception: distinguishing tangible objects, combining them, joint perception, and incidental perception. Finally, the study confirms the evidence provided by Avicenna to prove the existence of common sense. It recommends that future researchers explore the origins of Avicenna's ideas by comparing them with those of Greek philosophers such as Plato and Aristotle, who influenced him. Such comparative studies may provide deeper insights into the development of Avicenna's ideas on common sense.